Gram-Scale Synthesis of β-Sulfonyl Styrenes - Chang, Meng-Yang; Wu, Yan-Shin; Hsiao, Yu-Ting (Synthesis, 2018)
A simple and gram-scale synthesis of β-sulfonyl styrenes has been developed starting from one-pot PPA (polyphosphoric acid)-catalyzed 1,1-diacetoxylation of arylacetaldehydes (ArCH2CHO) with acetic anhydride (Ac2O) followed by deacetoxylative sulfonylation of the resulting 1,1-diacetate intermediate with sodium sulfinates (RSO2Na) in good yields under solvent-free conditions.
Keywords: β-sufonyl styrenes; sodium sulfinates; arylacetaldehydes; gram-scale synthesis